1997
DOI: 10.1128/jb.179.22.7004-7010.1997
|View full text |Cite
|
Sign up to set email alerts
|

Use of steroids to monitor alterations in the outer membrane of Pseudomonas aeruginosa

Abstract: Testosterone (a strongly hydrophobic steroid) and testosterone hemisuccinate (a negatively charged derivative) were used as probes to investigate alterations in the outer membrane of Pseudomonas aeruginosa. Diffusion rates of the steroids across the lipid bilayer were measured by coupling the influx of these compounds to their subsequent oxidation by an intracellular ⌬ 1 -dehydrogenase enzyme. Wild-type cells of P. aeruginosa (strain PAO1) were found to be 25 times more permeable to testosterone than to testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…In contrast, lipid A from N. gonorrhoeae is acylated in a symmetrical manner, with both sugar residues carrying three hydrocarbon chains (645). This difference in the positions of the acyl chains, however, cannot be the cause of the presumed high permeability of the neisserial OM, because P. aeruginosa, whose OM bilayer is at least as impermeable as that of Salmonella (503), produces lipid A that also has the symmetrical pattern of acylation (735) (Fig. 14B).…”
Section: Different Lipid a Structures In Various Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, lipid A from N. gonorrhoeae is acylated in a symmetrical manner, with both sugar residues carrying three hydrocarbon chains (645). This difference in the positions of the acyl chains, however, cannot be the cause of the presumed high permeability of the neisserial OM, because P. aeruginosa, whose OM bilayer is at least as impermeable as that of Salmonella (503), produces lipid A that also has the symmetrical pattern of acylation (735) (Fig. 14B).…”
Section: Different Lipid a Structures In Various Organismsmentioning
confidence: 99%
“…This apparent impermeability later turned out to be the result of slow influx across the OM counteracted by active efflux (456). Nevertheless, when the diffusion rates of very hydrophobic test solutes, i.e., steroids, were measured experimentally by coupling their influx with oxidation in the cytoplasm (503,504), their diffusion across the OM was found to be about 2 orders of magnitude slower than the diffusion through typical cell membranes containing phospholipid bilayers, showing that, indeed, the lipid bilayer domain of OM is an effective barrier.…”
Section: General Structure Of Lpsmentioning
confidence: 99%
“…Indeed, enhanced sensitivity to antibiotics, detergents, and EDTA and leakage of periplasmic enzymes have been observed in deep rough mutants of Escherichia coli and Salmonella enterica serovar Typhimurium (19). In P. aeruginosa, the permeation of steroids has been shown to be increased up to 5.5-fold when the outer membrane contained defective LPS (38). Furthermore, both in vivo and in vitro studies have demonstrated that LPS plays a role in protein assembly (10,28,45).…”
mentioning
confidence: 99%
“…Accumulating evidence indicates that the OM of Gram-negative bacteria serves as a selective permeability barrier, because its asymmetric structure with lipopolysaccharides results in an unusually slow influx of hydrophobic compounds such as steroids (49). Previous investigations have revealed that the diffusion of steroids across the OM of nonsteroid-degrading Gramnegative bacteria was approximately 2 orders of magnitude slower than diffusion through a cytoplasmic membrane containing phospholipid bilayers (17,49).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Previous investigations have revealed that the diffusion of steroids across the OM of nonsteroid-degrading Gramnegative bacteria was approximately 2 orders of magnitude slower than diffusion through a cytoplasmic membrane containing phospholipid bilayers (17,49). Although steroids could passively diffuse through the OM bilayer of S. denitrificans, our current data disproved the crucial role of passive diffusion in the cholesterol uptake of S. denitrificans because of the following: (i) the cholesterol uptake efficiency of cholesterol-grown S. denitrificans cells was significantly higher than that of palmitate-grown S. denitrificans cells and other tested proteobacterial species; (ii) the steroid uptake pattern of cholesterol-grown S. denitrificans cells exhibited high substrate selectivity; and (iii) the cholesterol uptake of S. denitrificans is not enhanced by preincubation with EDTA.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%